Cheap amusements: Working women and leisure in turn-of-the-century New York - Peiss, Kathy Lee (Temple University Press, 1986)
Contenu: The Homosocial World of Working-Class Amusements -- Leisure and Labor -- Putting on Style -- Dance Madness -- The Coney Island Excursion -- Cheap Theater and the Nickel Dumps -- Reforming Working Women's Recreation.
Keywords: 1800-1899; 1900-1999; approches et analyses; cours; discipline; his4443; histoire; histoire des femmes*; histoire et politique; loisirs des femmes*; new york; premier cycle; périodes historiques; rapports sociaux de sexe; sciences humaines; sociologie; thématiques; travail; travail des femmes*